As transformações e as novas dinâmicas das paisagens rurais na Pampa Gaúcha: a região intermediária de Uruguaiana - Ramos, Vagner Guimarães (2024)
This research has as its central objective the understanding of the transformations and new dynamics of the rural landscapes of Pampa Gaúcho in the Intermediate Region of Uruguaiana [RIU]. It is a qualitative investigation, which, faced with the problem of research, as well as its objectives, was anchored in theoretical, documentary research and empirical activities, where we made use of semistructured interviews, on-site observation, field diary and photography. RIU is located in the Pampa Biome, which transcends borders and extends across the Temperate Zone of South America. The main vectors of these transformations are: the expansion of temporary farming areas, forestry and the technicalization and scientificization of pastoral activity. Using our methodological tools, we list some frontiers that slow down the advancement of capitalist agriculture in RIU: those related to the natural and technical aspects of the landscape; those of a sociocultural nature, linked to pastoral activity as a historical-cultural construction and; those linked to legislation and bureaucratic procedures. The inflationary movement in land prices, the demographic emptying of the fields, the shortage of labor, the unfeasibility of small production, the shrinking of cattle and sheep herds and the growing productive specialization contribute to the replacement of the soybean-cultivated pasture binomial, that is, croplivestock integration, through “full year” agricultural leasing. We therefore address a Pampa that remains complex and heterogeneous, in which pressure on natural resources increases, both in livestock areas and in those dominated by agriculture and forestry. It is believed that agricultural activities are moving towards economic protagonism by overcoming technical, natural, cultural and bureaucratic barriers [legislation] to the expansion of soybeans, cultivated pastures and other agricultural activities.